IN VITRO AND IN VIVO ASSESSMENT OF TOXIC EFFECTS OF PARTHENIUM HYSTEROPHORUS LEAVES EXTRACT - Aziz, Dr Tariq; Hussain, Adil; Ali Khan, Ayaz; Ali, Muhammad; Iqbal, Javid; Iqbal, Zafar; Shahzad, Muhammad (Journal of the Chilean Chemical Society, 2022)
Parthenium hysterophorus is an invasive plant variety found in around 50 countries. Phenolic compounds in the P. hysterophorus leaves, HPLC analysis was carried out. In addition, methanolic extract of P. hysterophorus leaves was evaluated for total phenolic content (TPC), total flavonoid content (TFC), DPPH free radical scavenging activity, and hemolytic activity. The leaves crude extract was orally administered to rabbits (n = 5) at four doses (10, 20, 40 and 80 mg kg–1) for 9 days and its effects on hematological and biochemical parameters were investigated. Statistical analysis was performed using GraphPad Prism 8.0 software. The HPLC data revealed the presence of Chlorogenic acid, Bis-HHDP-hex (pedunculagin), Morin, Ellagic acid, Rutin, Syringic acid, etc., which were detected at various retention times. Among these compounds, Ellagic acid was abundantly present with sample peak area of 9594.909 %. Total phenolic and flavonoid contents in the leaves extracts at a concentration of 80 μg were, 57.35 ± 4.12 μg GAE/μg and 39.44 ± 0.41 μg QE/μg. DPPH free radical scavenging activity was 72.82 % with IC50 value of 168 μg/μL at 80 μg of the extract. In the hemolysis assay, 200 μg of extract had highest cell inhibition of 76.90 % with IC50 >500. Significant (P<0.05) variation in the hematological and biochemical parameters was observed in the extract fed groups. It has been concluded that P. hysterophorus leaves extract had toxic effects on the hematological and biochemical parameters in rabbits which cause abnormal blood profile.